Guidelines and best practice recommendations on reproductive health services provision amid COVID-19 pandemic: scoping review - Lemi Belay Tolu; Garumma Tolu Feyissa; Wondimu Gudu Jeldu (BMC, 2021)
Abstract Background Policymakers and health professionals prefer to use summarized evidence of practice recommendations. The aim of this scoping review is therefore to identify available guidelines, consensus statements, the standard of practice, and practice recommendations on reproductive health service provision during the COVID-19 pandemics. Methods We searched guideline databases and websites of professional associations and international organizations working on sexual and reproductive health. We looked for practice recommendations on sexual reproductive health services (SRH) during COVID-19 pandemics. Additionally, we searched: MEDLINE, EMBASE, and Google Scholar. Data extraction was done by two independent reviewers using a customized tool that was developed to record the key information of the source that's relevant to the review question. The difference between the two authors on data extraction was resolved by discussion. Results A total of 21 records were included in the review. Identified recommendations were classified into thematic areas. The records addressed approaches to antenatal care, labour and delivery, postnatal care, safe abortion, contraception, gender-based violence, and artificial reproduction. Conclusions There were consistent consensus statements and recommendations that there should be access to sexual and reproductive health services like antenatal care (ANC), postnatal care (PNC), contraception service, safe abortion care, and clinical management of rape survivors during the COVID-19 pandemics with the concerted effort of service re-organization. The practice recommendations focus on innovative ways of service provision to minimize patient and staff exposure to COVID-19 as well as alleviate the burden on the health care system. These include utilizing telemedicine and community/home-based care or self-care.